Peering beneath the Canadian crust. Issue 6 (December 2016) - Gilligan, Amy; Bastow, Ian D; Boyce, Alistair; Petrescu, Laura; Liddell, Mitch; Darbyshire, Fiona A; Hawthorn, David; Lane, Victoria; Daly, Debra; Simpson, David; Heffler, David
Abstract : Amy Gilligan and researchers from the UK, Canada and the US take a deep look at the North American craton. Abstract : Amy Gilligan and researchers from the UK, Canada and the US take a deep look at the North American craton.